Analisis Pengaruh Kompetensi Individu dan Motivasi terhadap Kinerja Karyawan PT. Beta Setia Mega - Septiyani, Septiyani; Sanny, Lim (Binus Business Review, 2013)
This study has three objectives, first to determine the influence of individual competencies to employee performance, second to determine the influence of motivation on employee performance, and third to determine the influence of individual competencies and motivation on employee performance in PT. Setia Mega Beta. Typeof research used is associative research using SPSS 16 as analytical technique. The data were collected by survey through distribution of questionnaires to employees of PT. Setia Mega Beta. The results showed that individual competencies do not partially affect employee performance, motivation partially affects employeeperformance. In addition, individual competencies and motivation simultaneously affect employee performance.